(3GdQSGdI GdTQjaI aj efGSc GdMLs - (3GdcQcj, GdYGedj, CHh GdMSf, GdeMbb GdKGfj, Ydj Hf GdMSjf Hf YHO GdYGdj, J (B940 (3g`s ((3eMeO Hf aQL Gddg Hf ESeGYjd Hf Ydj Gdfaj GdJHQjRj GdaQhjs)
(3ChdgG (B:s
(3GdMeO ddg (B... (3agPg LedI JTed Ydi eG dG HO efg ef HjGf efGSc ML HjJ Gddg GdMQGe hRjGQI QShdg hBdg Ydjg hYdjge GdSdGe hVYJgG Ydi SHjd GdGNJUGQ HGdJeGS NdGUI HYV GdENhGf (B...s
(3BNQgG (B:s
... (3hMSf GdCOGA RjGQI bHhQge aef RGQge QZHI aj RjGQJge hJUOjbG HeG QZHhG ajg cGfJ CFeJge TaYGFge jhe GdbjGeI hdcf gPG BNQ eG ChQOfGgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe , ddRQcdj (B4/281s
(3GdPQjYI (B22 -169 (7029 )s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis